Peningkatan Keterampilan Menulis Teks Narasi Menggunakan Model Cooperative Integrated Reading and Composition (CIRC) di Kelas IV SD Negeri 07 Pasaman Kabupaten Pasaman Barat - Hariaty, Yulina Desri; Sukma, Elfia (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve narrative text writing skills using the Cooperative Integrated Reading and Composition (CIRC) learning model in grade IV of SD Negeri 07 Pasaman, West Pasaman Regency. The CIRC model is applied to encourage students to improve their narrative text writing skills. This research was carried out in two cycles with the stages of planning, implementation, observation and reflection. The research subjects were grade IV students of SD Negeri 07 Pasaman, with data collected through test and non-test techniques, while the research instruments were through test sheets and non-tests. Data analysis was carried out using the percentage formula. The results show that the use of the CIRC model can significantly improve narrative text writing skills. In the first cycle, the average score in the aspect of the Teaching Module 90 with qualification (A), increased in the second cycle, namely obtaining an average of 95 with qualification (A), the results of the observation of the teacher aspect and the student aspect of the first cycle of the first meeting obtained the same score, namely 83.33 with good qualifications (B) and increased in the first cycle of the second meeting to 87.5 in the aspect of teachers and students. The average score for teacher and student activities in the first cycle of meetings I and II was 85.41 with Good (B) qualifications. In the second cycle, scores for teacher activities were obtained of 95.83 and student activities of 95.83 with very good qualifications (A).